HAK ATAS INFORMASITERHADAP PERLINDUNGAN HUKUMBAGI KONSUMEN DALAM JUAL BELIONLINE MELALUI LAZADA - Wardiono, Kelik; Firmansyah, Ifan (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
This study aims to describe consumers' rights to information in buying and selling transactions online on E-Commerce Lazada, this research uses the method approach sociological juridical (law in action). Source of data in this research is library data (library research) which consists of information on goods traded by business actors on E-Commerce Lazada. The data obtained through the literature study, after being processed, was analyzed qualitative by using deductive logic method. Based on the discussion conducted, it can be seen that the information contained in E-Commerce Lazada has not provided consumer protection, this is because there are still many business actors who provide information contrary to Law No. 8 of 1999 concerning Consumer Protection such as incorrect information, no guarantee of compensation to consumers, physical goods that do not match the information, and the information provided is incomplete. As well as the consequences in the form of administrative sanctions for business actors who violate the provisions of the Consumer Protection Act. Keywords: Information Rights, Consumer Protection, E-Commerce